Development of PJBL-STEM based E-books Assisted by Geometry Calculator to Foster Students' Critical Thinking Ability - Astutik, Iin Dwi; Pramasdyahsari, Agnita Siska; Setyawati, Rina Dwi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
A characteristic of students in 21st century learning is critical thinking, having the ability & willingness to digital literacy, ICT and new media, as well as adaptive and flexible initiative. However, currently, junior high school students' critical thinking abilities are still at a low level. Therefore, this research aims to develop e-book mathematics learning media based on PjBL-STEM assisted by Geometry Calculator to improve students' critical thinking skills. This type of research is research and development using the ADDIE development model which includes five stages, namely analysis, design, development, implementation and evaluation. The research subject was MTs NU Mranggen class VIII. The research instruments were material validation questionnaires, media validation questionnaires, and student critical thinking tests. The research results showed that (1) The media was declared suitable for use according to material experts, the validity level of the three material experts was 82%, 86% and 93%, while the validity level of the two media experts was 86% and 92%. (2) The average score for the experimental class was 81.04 while the control class was 64.96, so the learning media was declared effective. This research is very useful for improving students' critical thinking skills through developing a PjBL-STEM based e-book with the help of a Geometry Calculator on circle material used in learning. The unique thing about this research is that it is easier for students to learn because they use e-books which can be read anywhere and anytime. Apart from that, the e-book contains the PjBL-STEM learning method with the help of a Geometry Calculator which can make it easier for students in the learning process. Suatu karakteristik siswa pada pembelajaran abad 21 yaitu berpikir kritis, memiliki kemampuan & kemauan literasi digital, ICT dan media baru, serta terinisiatif yang adaptif dan fleksibel. Namun saat ini, kemampuan berpikir kritis siswa SMP masih pada tingkatan rendah. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan media pembelajaran matematika e-book berbasis PjBL-STEM berbantuan Geometry Calculator untuk meningkatkan kemampuan berpikir kritis siswa. Jenis penelitian ini adalah penelitian dan pengembangan dengan menggunakan model pengembangan ADDIE yang meliputi lima tahapan yaitu analisis, desain, pengembangan, implementasi dan evaluasi. Subjek penelitian adalah MTs NU Mranggen kelas VIII. Instrumen penelitian berupa validasi angket materi, validasi angket media, dan tes berpikir kritis siswa. Hasil penelitian menunjukkan bahwa (1) Media dinyatakan layak pakai menurut ahli materi, tingkat validitas ketiga ahli materi adalah 82%, 86% dan 93%, sedangkan tingkat validitas kedua ahli media adalah 86% dan 92 %. (2) Hasil nilai rata-rata kelas eksperimen 81,04 sedangkan kelas kontrol 64,96 sehingga media pembelajaran dinyatakan efektif. Penelitian ini sangat berguna untuk meningkatkan kemampuan berpikir kritis siswa melalui pengembangan e-book berbasis PjBL-STEM berbantuan Geometry Calculator terhadap materi lingkaran yang digunakan dalam pembelajaran. Hal unik dari penelitian ini yaitu siswa lebih mudah untuk belajar karena menggunakan e-book yang dapat dibaca dimanapun dan kapanpun. Selain itu, e-book tersebut di dalamnya memuat metode pembelajaran PjBL-STEM yang berbantuan Geometry Calculator yang dapat memudahkan siswa dalam proses pembelajaran.